Start Up Digital Business: Knowing Business Opportunities And Tips For Beginners - Fauziah, Zaleha; Hayadi, Bambang Herawan; Meria, Lista; Hasanah, Ananda Uswatun (Startupreneur Business Digital (SABDA Journal), 2022)
Start-up is a modern entrepreneurship form designed to realize original business ideas, mostly based on new technologies and the Internet. It evolves in the development cycle, which is determined by the business idea development cycle and the financing cycle. The purpose of the paper is to describe and analyze the business idea. The business idea is characterized by its content, circumstances of its origin, degree of originality and evidence of this originality. Start-ups are dominated by business ideas based on the application of information and communication technologies, the business idea is most often created by combining professional and business experience, but its originality is from the international point of view only average and the level of legal protection is quite rare. Various risks can pursue corporate actors. Everyone has to have an entrepreneur and business spirit. However, if you can grow and innovate, the business will certainly be very beneficial. For those who are trying to start a business, there are some business learning tips for beginners who are trying to build their business. The term startup is often associated with a company that has just been established or developed, and usually refers to an organization that has not functioned for a long time and is synonymous with a technology-related company. Due to the high mobility of human beings, in the world of commerce, we must be able to quickly provide services and products in response to consumer demand. Startup businesses are focused on providing solutions to specific problems or what is also known as problem-solving by further leveraging technology. Therefore, seriousness and unique understanding are required, including the secrets to starting this business.